ITS rDNA gene analysis versus MALDI-TOF MS for identification of Neoscytalidium dimidiatum isolated from Onychomycosis and Dermatomycosis cases in Medellin (Colombia) - Flórez-Muñoz, Sindy V. (2019)
Within the Neoscytalidium genus, N. dimidiatum, N. oculus, N. orchidacearum, and N. novaehollandiae have been recognized. Although these species are frequently found in soil, N. dimidiatum has been identified as an etiologic agent of onychomycosis or dermatomycosis, and N. oculus has been identified as an etiologic agent of an ocular lesion. All these species can be cultured in vitro, but their morphological identification by macroscopic and microscopic traits is difficult and imprecise due to their similarity. In this study, 34 isolates of Neoscytalidium spp. from 32 onychomycosis and two dermatomycosis cases in Medellin (Colombia) were identified at the species level using sequencing of the ITS1+5.8S+ITS2 nuclear rDNA region and MALDI-TOF mass spectrometry (MS). Neoscytalidium dimidiatum strain MUM 17.21 was used to construct the reference spectrum in the in-house library to identify the clinical isolates by MALDI-TOF MS. Additionally, N. dimidiatum PPC-216 and PLAB-055 strains were used to validate the in-house constructed reference spectra. Although four groups were observed in the dendrogram obtained from the proteins of each isolate profile, MALDI-TOF MS and sequencing results are in accordance, since all isolates were identified as N. dimidiatum.